Biomechanics of Urinary Bladder: State of Accommodation or Instability of Detrusor Pressure by Spontaneous Contractions during Slow-Filling and Slow-Emptying Cystometry - Duyl, W.A. Van (Research Perspectives of Microbiology and Biotechnology Vol. 7, 2024)
Autonomic slow emptying of not-stimulated pig bladders in-vitro via a flow resistor is described and is compared with clinical slow-filling cystometry in relation to the generation of spontaneous contraction activity and to the accommodation of detrusor pressure to bladder volume. Accommodation, conceived as an autonomic property of the bladder, is based on dynamic equilibration between passive elongations and active transient tiny contractions or micromotions. The transient character of the spontaneous contractions is crucial for the maintenance of a stable accommodated state of a bladder. Bladder volume V is virtually separable in elastic volume VE and rest volume VR. In an accommodated state ratio VE /VR depends on the mechanical state of bladder tissue, determined by its history of elongations and contractions. The principle difference between clinical compliance C and elastic compliance CE is demonstrated. The variable mechanical state of the tissue, in particular, expressed in variable elastic compliance CE, is explained by a network representing the mechanical states of the sliding filaments in the smooth muscle cells of bladder tissue.